Introducing medieval biblical interpretation : the senses of scripture in premodern exegesis - Levy, Ian Christopher (Grand Rapids, MI. Baker Academic, 2018)
This introductory guide, written by a leading expert in medieval theology and church history, offers a thorough overview of medieval biblical interpretation. After an opening chapter sketching the necessary background in patristic exegesis (especially the hermeneutical teaching of Augustine), the book progresses through the Middle Ages from the eighth to the fifteenth centuries, examining all the major movements, developments, and historical figures of the period. Rich in primary text engagement and comprehensive in scope, it is the only current, compact introduction to the whole range of medieval exegesis.
Introduction -- The age of the fathers -- The early Middle Ages -- The schools of the eleventh century: from Bec to Reims -- The monks of the twelfth century -- The school of St. Victor -- The schools of the twelfth century: from Laon to Paris -- Exegesis in the universities of the later Middle Ages -- Applied exegesis: the New Testament and the medieval papacy -- Conclusion: Can medieval exegesis speak to us today?
Includes bibliographical references and indexes.
Keywords: Bible -- Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.; Criticism, Medieval